Modeliranje rezultatov Proctorjevega preskusa - Pavšič, Primož (Materiali in tehnologije, 2003)
In civil engineering, soils and unbound granular materials are common materials. Whenever these materials are used for road construction, embankments, or as fill material, it is nearly always necessary to compact it to a dense state to obtain satisfactory engineering properties. Compaction on site is usually done by rolling, vibrating or ramming. Control of the degree of compaction is necessary to achieve a satisfactory result at a reasonable cost. A laboratory compaction test, known as the Proctor test, provides the basis for the control procedures used on site.
Keywords: civil engineering; gradbeništvo; geomehanika; geotehnika; Proctorjev preskus; modeliranje